(untitled) (Proceedings of the International Conference on Agriculture, 2022)
Heavy metals are the stress factors that cause important problems in plant production and environment. Among the heavy metals that cause a decrease in plant growth and development, lead can have an important effect depending on its concentration. Higher concentrations in root rhizosphere can negatively impact plant growth and yield. In this study, parameters related to plant growth were investigated in beans grown in soil contaminated with lead at different concentrations (0, 1000, 1500, 2000 mg kg-1). The potting soil prepared in the greenhouse study was first treated with the indicated doses of lead and left to incubate for three weeks, and then seeds were sown in to the pots. In the study, the effect of lead application was evaluated on stem diameter, plant height, leaf area, leaf fresh weight, shoot fresh weight, root fresh weight, leaf dry weight, shoot dry weight, root dry weight, SPAD value, chlorophyll a, chlorophyll b, total chlorophyll, electrical leakage (EL) and leaf relative water content (LRWC) of bean seedlings. Findings of the study indicated that there was a significant decrease in growth and chlorophyll contents of bean seedlings in parallel with the increased lead dose. Also, with increasing lead level, LRWC decreased while EL increased. As a result, it has been determined that lead led to reduce in growth and development in bean seedlings, and seen that in the next stage, it will cause significant reductions in yield leads to economic loss of income for the producer.